POLITIK LOKAL : POTRET PENYELENGGARA PEMILU DALAM PUTUSAN SIDANG DEWAN KEHORMATAN PENYELENGGARA PEMILU DI KALIMANTAN TIMUR TAHUN 2018-2020 - Mohammad Taufik (Magister Administrasi Publik FISIP Universitas Mulawarman, 2021)
The integrity of the election organizers in enforcing the rules of ethics for election organizers is still very far from what it should be. Therefore, does the portrait of general election organizers looks beautiful in case of ethics or vice versa. The duties and authorities of DKPP (Honorary Council for General Election Organizers) relate to individual election organizers, both KPU and Bawaslu. Ethical cases in running the general election process have often been encountered in every electoral event in Indonesia. The lack of discipline of an organizer in carrying out their duties and functions causes these organizers to deal with cases of organizers code of ethics. Ethics is an important element that must be obeyed by every election organizer because it is one of the fundamental aspects in realizing democratic elections. Therefore, to uphold the Code of Ethics for election administrators, the Honorary Council of General Elections (DKPP) was formed, aiming to maintain the independence, integrity, and credibility of the KPU and Bawaslu that the General Election will certainly run well and correctly.Keywords: Local Politics, Election Organizer, DKPP, East Kalimantan